Human Papillomavirus (HPV) prevalence in population younger than 12 years old: A meta-analysis and systematic review - Mona Sadat Larijani; Amir Javadi; Amirabbas Faridpour; Mohammad Banifazl; Fatemeh Ashrafian; Anahita Bavand; Ladan Moradi; Amitis Ramezani (Journal of Infection and Public Health)
Background: The prevalence of HPV in children has been studied in different populations; however, the heterogeneity between the investigations is remarkable, and the total prevalence of HPV infection in this population is not well understood. Methods: The conducted studies on the prevalence of HPV infection in the population < 12 years old were explored and analyzed through a systematic review and meta-analysis approach. The studies which investigated HPV detection in oropharyngeal, nasopharyngeal and/or anogenital samples were included. HPV prevalence, sample type and age were considered as the inclusion criteria for the meta-analysis. Results: Fifteen published studies between 1994 and 2021 with a total number of 2638 children aged from 1 day to 12 years, were analyzed. The total HPV prevalence in this population is estimated to be 14.7 % with the highest rate in kids over 1 year old, accounting for 25.4 %. Furthermore, the type of samples showed that buccal swabs had the highest rate of infection. The ratio of HPV-positive children born to HPV-positive mothers varied from 3 % to 55 % (median: 17.5 %), while this ratio decreased to 0–19.7 % (median 5.55 %) in HPV-positive kids born to HPV-negative mothers. Conclusion: According to the present analysis, the prevalence of HPV in children is relatively high and requires further prospective studies and monitoring HPV acquisition in the young population, specifically in those born to HPV-positive mothers. Follow-up studies to assess the persistency rate of HPV after infancy are needed in order to highlight any possible implications for HPV vaccination programs and policy-making.